Sri Lanka : Staff Report for the 2002 Article IV Consultation and Final Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Sri Lanka's 2002 Article IV Consultation and Final Review Under the Stand-By Arrangement (SBA). Performance under the SBA has been satisfactory, although there are pressures on the budget. All the quantitative performance criteria for end-April 2002 were met and the structural benchmarks completed, albeit with a small delay. Fiscal revenue performance was reasonable in the first half of the year, and the new value-added tax was introduced (after some delay) from August. The authorities have also taken several important steps on their structural reform agenda.